Los hueseros Escobar. Hibridación entre la medicina tradicional y la biomedicina en Cochabamba, Bolivia - Pedro Pablo Salvador Hernandez (Centre de Recherches sur les Mondes Américains, 2011)
This article examines the treatment of the phenomenon of health and illness in the context of cultural hybridization within Escobar bonesetter’s clinic in the municipality of Cliza, in Cochabamba (Bolivia). It addresses the characteristic features of their therapy that combines purely mechanical and "innovative" ingredients (belonging to the field of traditional medicine) as ’Escobar handling’ applied to a herniated disc, with elements that contribute to the symbolic effectiveness of their treatments, as ’express diagnostic’ and ’positive programming’. It also studies the relationship established with biomedicine by the experience of the last generation of bonesetter’s and their hinge role of translators and interpreters from different medical systems.